HUBUNGAN GAYA KEPEMIMPINAN DENGAN MOTIVASI KERJA, KINERJA PEGAWAI, DAN PERSEPSI K3 DI IPA PDAM SAMARINDA - Anggi Triwardani; Iwan M Ramdan; Rahmat Bakhtiar (Husada Mahakam, 2020)
ABSTRACT The success of a company is supported by the role of a leader with his leadership style. The application of leadership is very influential on employee work motivation because to meet their needs requires the support from a leader. Occupational safety and health (OHS) programs are very important because when employees give a good perception of occupational safety and health programs, OHS behavior tends to be good. The purpose of this study was to determine the relationship of leadership style with work motivation, employee performance, and health safety perception in Cendana Water Treatment Plant of PDAM Tirta Kencana, Samarinda City. This type of analytic survey research with cross sectional approach was conducted in July 2019. The research sample of 54 people (total sampling) and data analysis using Pearson correlation test with significance level (α<0,05). The results showed that as many as 34 employees rated the authoritarian leadership style with most employees having low and high motivation (p-value 0,022), as many as 20 employees having moderate performance (p-value 0,008), as many as 21 employees having good OHS perceptions (p-value 0,000). It was concluded that there was a relationship between leadership style with work motivation, leadership style with employee performance, and leadership style with K3 perception in Cendana Water Treatment Plant of PDAM Tirta Kencana, Samarinda City. The leader must be able to apply a more effective leadership style, for example applying a democratic leadership style that always receives input and advice from his subordinates. Keywords: Leadership, Performance , Motivation, Perception